The Effect of Genistein, L-carnitine and their combination on gene expression of hepatocyte PPAR-α and CPT-1 in experimental nephrotic syndrome - Yousefinejad, Abbas; Siassi, Fereydoon; Mirshafiey, Abbas; Koohdani, Fariba; Javanbakht, Mohammad-Hassan; Sedaghat, Reza; Ramezani, Atena; Mohammadi, Hamed; Zarei, Mahnaz; Djalali, Mahmoud (Progress in Nutrition, 2019)
Objective: One of the disorders that occur in nephrotic syndrome would be hyperlipidemia. L-carnitine and genistein have the capability to control this syndrome by changing in lipid metabolism. In the present study, we delved into the effects of Genistein and L-carnitine on the PPAR-α and CPT-1 gene expressions in experimental nephrotic syndrome. Methods: In controlled experimental study, 50 male Sprague–Dawley rats were randomly divided into five groups consisting of 10 animals each with similar mean body weights (300±50 g): NC (normal-control), PC (patient-control), LC (L-carnitine), G (genistein), and LCG (L-carnitine-genistein). The spot urine samples were collected, and urine protein-to-creatinine ratio was measured. Hepatocytic RNA was extracted and real-time PCR was used for PPAR-α and CPT-1 gene Expression measurement. Results: At the end of the study, final weight of the patient groups was considerably lower than the NC group (P=0.001), and weight gain of the NC group was higher than the other groups (P